KONSEPESI PENDIDIKAN KARAKTER DALAM PERSPEKTIF ISLAM - Nurma Ali Ridlwan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Moral / character education is a need in the midst of the people who areafflicted by the multidimensional crisis, especially moral crisis. The realization ofthe student / child who has character (in terms of religion, to have â€œakhlaqulkarimahâ€) is the desire of all people, especially for parents and teachers.Education is an effective place in building the character of students. Thefocus in this research is carried out on character education in Elementary Schoolof Al-Irsyad Al-Islamiyah 01 Purwokerto. Elementary School (Sekolah Dasar =SD) Al-Irsyad Al-Islamiyah 01 Purwokerto as an educational institution, strivesearnestly in educating students through character education program called MoralEducation Program (Program Pendidikan Akhlak = PPA).